Synthesis and Antidepressant Activity of Some 3-(3’’-Coumarinyl)-1,5-diphenyl-2-pyrazolines and 3-(2’’- hydroxy naphthalen-1’’-yl)-1,5-diphenyl-2-pyrazolines - RAJENDRA PRASAD, Y.; RAVI KUMAR, P.; ASHA DEEPTI, CH.; RAMANA, M.VENKATA (Asian Journal of Chemistry, 2010)
Five new 3-(3''-coumarinyl)-1,5-diphenyl-2-pyrazolines (3a-e) were synthesised by reacting 3-[1-oxo-3-(substituted phenyl)-2-propenyl]-2H-1-benzopyran-2-ones (2a-e) with phenyl hydrazine hydrochloride and another five new 3-(2''-hydroxy naphthalen-1''-yl)-1,5-diphenyl-2-pyrazolines (5a-e) were synthesized by reacting 1-(2'-hydroxynaphthyl)-3-phenyl-2-propene-1-one (4a-e) with phenyl hydrazine hydrochloride. All these compounds were characterized by means of their IR, 1H NMR spectroscopic data and microanalyses. The antidepressant activity of these compounds was evaluated by the Porsolt behavioural despair test on Swiss-Webster mice. 3-(3''-coumarinyl)-1-phenyl-5-(2',4',5'-trimethylphenyl)-2-pyrazoline (3a), 3-(3''-coumarinyl)-1-phenyl-5-(4'-hydroxy-3'-methoxyphenyl)-2-pyrazoline (3d), 1-phenyl-3-(2''-hydroxynaphthalen-1''-yl)-5-(2',4',5'-trimethoxyphenyl)-2-pyrazoline (5c) and 1-phenyl-3-(2''-hydroxynaphthalen-1''-yl)-5-(4'-dimethylaminophenyl)-2-pyrazoline (5a) reduced 36.59-59.65 % immobility times at 100 mg kg-1 dose level. It was observed that some of the 2-pyrazolines derived from 3-acetyl coumarin showed grater activity than those derived from 2-hydroxy-1-acetonaphthone. In addition it was found that the compounds possessing electron releasing groups such as dimethyl amino, methoxy and hydroxyl substituent, on both the rings at position 3 and 5 of pyrazolines, considerably enhanced the antidepressant activity when compared to the pyrazolines having no substituents on the rings.